Efektivitas Modul STEM Inklusif Berbasis SDGs terhadap Keterampilan Proses Sains Siswa Slow Learner di Kawasan Lahan Gambut - Kistiono; Muhammad Yusup; Sudirman; Kiki Ayu Winarni; Putri Angelina (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of an inclusive STEM module based on the Sustainable Development Goals (SDGs) in improving science process skills (SPS) among slow learner students in a peatland region. A quasi-experimental pretest-posttest control group design was employed with 78 Grade 8 slow learners from SMP Negeri 1 Pemulutan Barat, South Sumatra. The module, developed using the ADDIE model, focused on water filtration and peatland water quality within the context of SDG 6 (Clean Water and Sanitation). The core science topics covered included pH measurement, mechanical filtration, separation of mixtures, and colloidal properties of peat water. It was validated by experts in content, pedagogy, and inclusivity. Data were analyzed quantitatively using independent t-tests, normalized gain (N-Gain), and effect size (Cohen’s d), as well as qualitatively through classroom observations and semi-structured interviews. Results revealed that the experimental group achieved a mean N-Gain of 0.79 (high category), compared to 0.42 (medium category) for the control group. Statistical analysis indicated a significant difference between the groups (t = 5.68; p < 0.001; Cohen’s d = 1.28). Qualitative findings further demonstrated that students reported increased confidence and motivation, attributing these improvements to the module’s use of visual illustrations, locally relevant contexts, and scaffolded instructions. These findings suggest that an inclusive, SDG-based STEM module is effective in improving SPS among slow learner students. This study contributes to the growing body of literature on inclusive STEM education by illustrating how integrating the SDGs within a local ecological context can foster equitable and meaningful science learning.